Idealitas Weight and Balance pada Pesawat Tipe Comac ARJ21-700 Maskapai TransNusa di Bandar Udara Internasional Soekarno-Hatta - Nurul Hikmah; Dhiani Dyahjatmayanti (MES Bogor, 2024)
The calculation of weight and balance requires high accuracy so that the flight can be carried out safely to the destination airport. A number of obstacles that load control officers experience can affect the ideality of weight and balance and must be properly calculated. The purpose of this research is to determine the ideal weight and balance of Comac ARJ21-700 aircraft of TransNusa airline at Soekarno-Hatta International Airport. This research uses qualitative and quantitative methods using primary data obtained through observation and interviews, secondary data using documentation and literature studies. Data collection techniques used by observation, interviews and documentation. Interviews were conducted with supervisors and senior load control narrow body and junior load control. Data analysis techniques by means of data collection, data reduction, data presentation, and conclusion drawing. The results of this study are the obstacles of load control officers in calculating the weight and balance of Comac ARJ21-700 aircraft of TransNusa airline, namely the delay of check-in officers in inputting data on the number of passengers and luggage. Determination of the location of passengers and luggage is carried out by check-in officers, if there is a mismatch, the load control officer makes a request to the check-in officer to maximize the front compartment. The average center of gravity of the Comac ARJ21-700 shows at -7.29UP which states that the center of gravity of the Comac ARJ21-700 is -7.29UP.